Impact Assessment of School WASH Programme on Students’ Health and Hygiene Conditions in Rural Mardan, Pakistan: WASH Programme Impacts Assessment in Rural Mardan - Baig, Shams Ali; Khan, Zarish; Qasim, Muhammad; Baig, Muzaffar Ali; Khan, Attaullah; Shams, Dilawar Farhan; Idress, Muhammad (Proceedings of the Pakistan Academy of Sciences: B. Life and Environmental Sciences, 2018)
The implementation of water, sanitation and hygiene (WASH) programme in schools with true its spirit can largely solve the issues related to poor water quality, sanitation, health and hygiene conditions, which resultantly improve children attendance and hygienic environment in schools. In the present study, an attempt has been made to investigate the impacts of WASH programme on student health and hygiene condition in selected schools in district Mardan, Khyber Pakhtunkhwa, Pakistan. Social surveys including questionnaire, personal interview, focus group discussion (FGD) and personal observation were carried out to collect the data related to WASH activities.Drinking water samples were collected and analyzed from the targeted schools for different physical, chemical and bacteriological parameters including electrical conductivity (EC), pH, total dissolved solids (TDS), turbidity, E. coli, and total coliform. Statistical analyses, like descriptive statistics (i.e. ANOVA) were applied to analyze the data. The data collected using different social survey methods showed that the hygiene conditions in schools were not up to the standard, number of latrines in each school was not enough and no hand washing with soap was found practicing in each school. As a result, the number of children suffering from water borne diseases including diarrhea was higher as compared to other diseases. Water quality descriptive statistical analysis revealed that all the parameters were significantly different (P < 0.05) and uniformly contribution to the overall contaminant loads in the water samples, except the water pH values. Findings from the present study suggested that WASH programme is effective for promoting health and hygiene education in school going children.